MMS Observations of Reconnection at Dayside Magnetopause Crossings During Transitions of the Solar Wind to Sub‐Alfvénic Flow. Issue 10 (9th October 2017) - Farrugia, C. J.; Lugaz, N.; Alm, L.; Vasquez, B.; Argall, M. R.; Kucharek, H.; Matsui, H.; Torbert, R. B.; Lavraud, B.; Le Contel, O.; Cohen, I. J.; Burch, J. L.; et al.
Abstract: We present MMS observations during two dayside magnetopause crossings under hitherto unexamined conditions: (i) when the bow shock is weakening and the solar wind transitioning to sub‐Alfvénic flow and (ii) when it is reforming. Interplanetary conditions consist of a magnetic cloud with (i) a strongB (∼20 nT) pointing south and (ii) a density profile with episodic decreases to values of ∼0.3 cm −3 followed by moderate recovery. During the crossings the magnetosheath magnetic field is stronger than the magnetosphere field by a factor of ∼2.2. As a result, during the outbound crossing through the ion diffusion region, MMS observed an inversion of the relative positions of the X and stagnation (S) lines from that typically the case: the S line was closer to the magnetosheath side. The S line appears in the form of a slow expansion fan near which most of the energy dissipation is taking place. While in the magnetosphere between the crossings, MMS observed strong field and flow perturbations, which we argue to be due to kinetic Alfvén waves. During the reconnection interval, whistler mode waves generated by an electron temperature anisotropy ( T e ⊥ > T e ∥ ) were observed. Another aim of the paper is to distinguish bow shock‐induced field and flow perturbations from reconnection‐related signatures. The high‐resolution MMS data together with 2‐D hybrid simulations of bow shock dynamics helped us to distinguish between the two sources. We show examples of bow shock‐related effects (such as heating) and reconnection effects such as accelerated flows satisfying the Walén relation. Key Points: We examine dayside magnetopause reconnection when the bow shock is weakening and reforming The relative position of the X and S lines is inverted Kinetic Alfven waves are seen associated field and flow perturbations in the magnetosphere